1984
DOI: 10.1073/pnas.81.22.7243
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation increases phosphorylation of tyrosine hydroxylase in superior cervical ganglion of rat.

Abstract: Electrical stimulation of the superior cervical ganglion of the rat increased the phosphorylation of tyrosine hydroxylase (tyrosine 3-monooxygenase, EC 1.14.16.2) in this tissue. Ganglia were incubated with [32pJp1 for 90 min and were then electrically stimulated via the preganglionic nerve. Tyrosine hydroxylase was isolated from homogenates of the ganglia by immunoprecipitation followed by polyacrylamide gel electrophoresis. 32P-labeled tyrosine hydroxylase was visualized by radioautography, and the incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Subsequently, treatment of intact catecholaminergic cells with either cyclic AMP analogues or secretagogues was shown both to phosphorylate and to activate tyrosine hydroxylase in association with an acceleration of catecholamine biosynthesis (Meligeni et ai., 1982;Haycock et al, 1982~). To date, stimulation-dependent phosphorylation of tyrosine hydroxylase has been demonstrated in a number of intact tissues, including vas deferens, adrenal medulla, PC-12 cells, superior cervical ganglion, and intact and ''leaky'' adrenal chromaffin cells Meligeni et al, 1981;Cahill and Perlman, 1984;Yanagihara et al, 1984;Niggli et al, 1984). Taken together, the data strongly suggested that cyclic AMP-dependent phosphorylation of tyrosine hydroxylase is an important process in regulating catecholamine biosynthesis.…”
Section: Known Proteinsmentioning
confidence: 95%
“…Subsequently, treatment of intact catecholaminergic cells with either cyclic AMP analogues or secretagogues was shown both to phosphorylate and to activate tyrosine hydroxylase in association with an acceleration of catecholamine biosynthesis (Meligeni et ai., 1982;Haycock et al, 1982~). To date, stimulation-dependent phosphorylation of tyrosine hydroxylase has been demonstrated in a number of intact tissues, including vas deferens, adrenal medulla, PC-12 cells, superior cervical ganglion, and intact and ''leaky'' adrenal chromaffin cells Meligeni et al, 1981;Cahill and Perlman, 1984;Yanagihara et al, 1984;Niggli et al, 1984). Taken together, the data strongly suggested that cyclic AMP-dependent phosphorylation of tyrosine hydroxylase is an important process in regulating catecholamine biosynthesis.…”
Section: Known Proteinsmentioning
confidence: 95%
“…52, 1517-1522 (1989). (Lee et al, 1985;McTigue et al, 1985;Tachikawa et al, 1987), superior cervical ganglia (Cahill and Perlman, 1984), and CNS fragments or synaptosomes (Porter, 1986;Haycock, 1987). The phosphorylation of TH is consistently associated with an increase in enzyme activity (for review, see Goldstein and Greene, 1987).…”
mentioning
confidence: 99%
“…Tyrosine hydroxylase [TH; tyrosine 3-monooxygenase; L-tyrosine tetrahydr0pteridine:oxygen oxidoreductase (3-hydroxylating); EC 1.14.16.21 is the rate-limiting enzyme in the biosynthesis of catecholamines (Levitt et al, 1965;Molinoff and Axelrod, 1971;Kaufman and Kaufman, 1985). Besides the regulation of TH activity by posttranslational phosphorylation (Cahill and Perlman, 1984;Campbell et al, 1986;Cremins et al, 1986; for review, see Kaufman and Kaufman, 1989, TH synthesis is regulated by neuronal activity (transsynaptic induction) (Thoenen et al, 1969(Thoenen et al, , 1979Joh et al, 1973;Thoenen, 1975;Zigmond, 1985), nerve growth factor (Thoenen et al, 1971(Thoenen et al, , 1979(Thoenen et al, , 1985Acheson et al, 1984), glucocorticoids (Otten and Thoenen, 1975;Thoenen and Otten, 1978;Thoenen et al, 1979), laminin , and cell-cell contact (Acheson and Thoenen, 1983;Saadat and Thoenen, 1986;Saadat et al, 1987).…”
mentioning
confidence: 99%